Assessment of RANS-based turbulence model for forced plume dynamics in a linearly stratified environment. (15th March 2022) - Kumar, Nitin; Mukherjee, Partho; Chalamalla, Vamsi Krishna; Dewan, Anupam; Balasubramanian, Sridhar
Abstract: We present a computational study on the dynamics of a forced plume released in a linearly stratified medium for a range of buoyancy frequencies N ∞ =0 - 0.7 s −1 . Three dimensional unsteady Reynolds-Averaged Navier–Stokes (RANS) simulations are performed using the standard k − ε turbulence model. The mean flow parameters such as the maximum height Z m, mean centerline velocity 〈 w c 〉, mean axial velocity 〈 w 〉, and turbulence parameters such as shear production ( P ), buoyancy production ( B ), and dissipation rate ( ε ) are compared with the experimental results of Mirajkar et al. (2020) and a good agreement is found. The validated model is then used to study the forced plume characteristics and energetics at various values of N ∞ . The passive scalar contours reveal that the plume reaches a maximum height in a stratified medium where the momentum becomes zero, then falls back to the neutral buoyancy height before spreading in the lateral direction. We also found that the maximum height reached by the plume decreases with increasing value of N ∞, consistent with the previous studies. Quantification of turbulence parameters reveal that the production flux, P, and viscous dissipation, ε, from the RANS computation are in reasonable agreement with the experimental values at N ∞ = 0.4 s −1 . Further, the residual, given by 〈 〈 P 〉 〉 + 〈 〈 B 〉 〉 - 〈 〈 ε 〉 〉, is found to be larger for higher N ∞, indicating more non-homogeneity in the flow at higher stratification. Overall, the RANS modeling is found to accurately predict the mean flow quantities, such as mean centerline velocity and maximum height reached by the plume. The comparison of the modeled turbulence quantities with experimental data seems satisfactory, but indicates a need for some improvement at high values of N ∞ . Highlights: Assessment of k- ɛ model is performed for forced plume in a stratified medium. Benchmarking of the turbulence model is done against the experimental data. The mean flow quantities are predicted well by the RANS model. Shear and buoyancy production increases with an increase in stratification. Higher TKE residual at higher N ∞, indicating the limitation of the turbulence model.